Investment outlook for the medium range tankers (MRs) segment from 2019 – 2023 - Dang, Thu Giang (2019)
This report aims to provide the freight market outlook for Medium-Ranged (MR) Tankers segment between 2019 and 2023 by. examining the key drivers of the market and performs a fundamental analysis on the direction at which the MR Tanker freight rate is heading to. It is established that freight rates are influenced by various demand factors including world economy, international Clean Petroleum Product (CPP) trade and refining capacity and throughput, while supply factors involve orderbook, new buildings and demolition. By examining the influence of these drivers on the freight market, it is forecasted that the rate will be between $7485/day and $10458/day. It can be deduced that the market is improving from a weak to a steadier situation, showing potential for investment. The freight band, along with the financial feasibility performed in Volume 1, will be used to evaluate different vessel employment scenario: time-charter ships or putting ships in the spot market. The evaluation will be done in volume 3 of the project